P3.166 High chlamydia and bacterial vaginosis burden in hiv epicentre in south africa. (8th July 2017) - Garrett, N; Ngubane, N; Osman, F; Naicker, N; Mitchev, N; Mlisana, K; Ngomane, N; Ngobese, H; Dlamini, N; Naidoo, J; Samsunder, N; Kharsany, A; et al.
Abstract : Introduction: As long as syndromic management of sexually transmitted infections (STI) remains the main model of care in low and middle income countries, diagnostic surveillance is essential for STI control, especially in high HIV incidence settings. Here, we present the baseline data from the CAPRISA 083 cohort study that was conducted in a large urban primary health care clinic in KwaZulu-Natal, South Africa. Methods: Women aged 18–40 presenting for syndromic STI care at the facility were assessed for participation. HIV positive women (prevalence 39.1%), pregnant women (9.1%) or those engaging in sex work were excluded due to pre-determined eligibility criteria. Women consenting to the study completed a sexual risk questionnaire, were examined by a nurse, and underwent point-of-care testing for chlamydia and gonorrhoea (Xpert CT/NG), trichomonas (OSOM rapid test), and microscopy to assess for bacterial vaginosis (BV) and candida. Gonorrhoea cases were further investigated for antibiotic resistance. Results: A total of 267 women, median age 23 (IQR 21–27), were enrolled and 88.4% reported to be symptomatic. All were sexually active and 75.7% stated that they used condoms with their partners, although only 3.7% used them consistently. 125 (46.8%) had abnormal pelvic examinations, including 106 (39.7%) women with vaginal discharge. STI testing revealed an 18.5% prevalence of chlamydia (20.5% in <25 year-olds), 5.2% gonorrhoea and 2.6% trichomonas. Two thirds of women (69.3%) had evidence of abnormal vaginal flora (33.7% BV and 35.6% intermediate flora) based on Nugent Score, and 17.6% were diagnosed with candida infection. A total of 52/267 (19.5%) reported symptoms, but had no STI or abnormal flora found. Of 9 specimen cultured for gonorrhoea resistance, 7 (77.7%) were resistant to penicillin and 4 (44.4%) to ciprofloxacin, but no cephalosporin resistance was identified. Conclusion: In this high HIV incidence setting, the burden of chlamydia infection and abnormal vaginal flora was concernedly high, warranting enhanced STI management strategies at population level. Support: : This work was NIH-funded (AI116759). Cepheid loaned two 4-module Genexpert machines to the study team free-of-charge, but did not contribute to the preparation of this abstract